Knowledge, Awareness and Practice with Antimicrobial Stewardship Programmes among Healthcare Providers in a Ghanaian Tertiary Hospital - Eneyi E. Kpokiri; Misha Ladva; Cornelius C. Dodoo; Emmanuel Orman; Thelma Alalbila Aku; Adelaide Mensah; Jonathan Jato; Kwadwo A. Mfoafo; Isaac Folitse; Araba Hutton-Nyameaye; Inemesit Okon-Ben; Paapa Mensah-Kane; et al. (MDPI AG, 2021)
Antimicrobial resistance (AMR) is a significant problem in global health today, particularly in low- and middle-income countries (LMICs) where antimicrobial stewardship programmes are yet to be successfully implemented. We established a partnership between AMR pharmacists from a UK NHS hospital and in Ho Teaching Hospital with the aim of enhancing antimicrobial stewardship knowledge and practice among healthcare providers through an educational intervention. We employed a mixed-method approach that included an initial survey on knowledge and awareness before and after training, followed by qualitative interviews with healthcare providers conducted six months after delivery of training. This study was carried out in two phases in Ho Teaching Hospital with healthcare professionals, including pharmacists, medical doctors, nurses and medical laboratory scientists. Ethical approval was obtained prior to data collection. In the first phase, we surveyed 50 healthcare providers, including nurses (33%), pharmacists (29%) and biomedical scientists (23%). Of these, 58% of participants had engaged in continuous professional development on AMR/AMS, and above 95% demonstrated good knowledge on the general use of antibiotics. A total of 18 participants, which included four medical doctors, five pharmacists, four nurses, two midwives and three biomedical scientists, were interviewed in the second phase and demonstrated greater awareness of AMS practices, particularly the role of education for patients, as well as healthcare professionals. We found that knowledge and practice with AMS was markedly improved six months after the training session. There is limited practice of AMS in LMICs; however, through AMR-focused training, we demonstrated improved AMS skills and practice among healthcare providers in Ho Teaching Hospital. There is a need for continuous AMR training sessions for healthcare professionals in resource-limited settings.